BIOATCTIVITY OF PHLORETIN FROM Syzgium polyanthum (WIGHT) WALP AS A GOUTY ARTHRITIS TREATMENT BASED ON SCREENING IN SILICO - Fernando Watung; Musma Rukmana; Hasmiati Hasmiati; Tika Putri Agustina; Margaret Pandaleke (Universitas Negeri Manado, 2023)
Gouty Arthritis is a disease caused by the accumulation of monosodium urate in the joints due to hyperuricemia, which causes painful inflammation. Syzgium polyanthum (Wight) Walp is a plant that grows in Indonesia and has been used as a traditional medicine. It is used to treat various diseases, especially excessive production of uric acid. It is thought to contain phloretin compounds which can reduce the amount of uric acid. The purpose of this study was observed the biological activity of the natural products phloretin as an antihyperuricemia. Bioinformatic applications used in this study include the Pubchem compound database, protein target data base (Pharmmapper and Swiss Target Prediction), molecular docking software PyRx 0.8, software for 3D visualization and analysis of docking ligands and binding sites PyMOL and BIOVIA Disvovery Studo Client 2016. The results of docking and binding site analysis showed that phloretin was able to interact with cyclin dependent kinase 2 (target protein) with a binding affinity of -6 kcal/mol more negatively than allopurinol with a binding affinity of -5.7, at different binding sites. Phloretin is a potential compound that can be used in the treatment of gouthy arthritis as an anti-inflammatory by inhibiting CDK2 activity.